2013
DOI: 10.1161/circimaging.112.000132
|View full text |Cite
|
Sign up to set email alerts
|

99m Tc-Pyrophosphate Scintigraphy for Differentiating Light-Chain Cardiac Amyloidosis From the Transthyretin-Related Familial and Senile Cardiac Amyloidoses

Abstract: Background Differentiating immunoglobulin light-chain (AL) from transthyretin-related cardiac amyloidoses (ATTR) is imperative given implications for prognosis, therapy, and genetic counseling. We validated the discriminatory ability of 99mTc-pyrophosphate scintigraphy (99mTc-PYP) in AL vs. TTR-related cardiac amyloidoses. Methods and Results 45 subjects (12 AL, 16 ATTR wild-type, and 17 ATTR mutants) underwent 99mTc-PYP planar and single-photon positive emission computed tomography (SPECT) cardiac imaging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
303
0
25

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 547 publications
(350 citation statements)
references
References 34 publications
4
303
0
25
Order By: Relevance
“…Moreover, the serum concentrations of total TTR in SSA patients did not differ from age, gender and ethnically matched controls or from a group of AL patients with significant clinical cardiac involvement [110]. Scintigraphy with Tc-pyrophosphate can help in differentiating transthyretin-related familial and senile cardiac amyloidoses from light chain cardiac amyloidosis [111,112]. However, the diagnosis of SSA requires endomyocardial biopsy, with demonstration that the deposited fibrils are constituted by TTR, in absence of mutated TTR by DNA sequencing.…”
Section: Measurement Of the Amyloidogenic Precursormentioning
confidence: 98%
“…Moreover, the serum concentrations of total TTR in SSA patients did not differ from age, gender and ethnically matched controls or from a group of AL patients with significant clinical cardiac involvement [110]. Scintigraphy with Tc-pyrophosphate can help in differentiating transthyretin-related familial and senile cardiac amyloidoses from light chain cardiac amyloidosis [111,112]. However, the diagnosis of SSA requires endomyocardial biopsy, with demonstration that the deposited fibrils are constituted by TTR, in absence of mutated TTR by DNA sequencing.…”
Section: Measurement Of the Amyloidogenic Precursormentioning
confidence: 98%
“…Planar imaging alone or with single-photon emission computed tomography (SPECT) using nonamyloid-specific, bone-avid radiotracers ( 99m Tc-DPD [3,3- [8][9][10][11][12][13][14][15][16][17] Recent data indicate that the increased level of microcalcifications may explain the enhanced affinity of bone-seeking tracers for TTR over AL amyloidosis. 18 Amyloidspecific, positron emitting 18 F-and 11 C-tagged tracers have been used successfully with positron emission tomography (PET) imaging for the identification of both AL and TTR subtypes of CA.…”
mentioning
confidence: 99%
“…Since the seminal work by Perugini et al 8 , a number of other studies have showed that 99m Tc-DPD and 99m Tc-PYP nuclear imaging is feasible and effective in detecting TTR-CA. 9,11,12,[15][16][17] In addition to the traditionally used qualitative Perugini score which compares myocardial to bone uptake and the semiquantitative HR:WBR, 8 Bokhari et al also showed that 99M Tc-PYP imaging with a heart-to-contralateral lung ratio of [1.5 detected TTR-CA with a 97% and 100% sensitivity and specificity, respectively. 16 Negative and positive example images of TTR-CA with 99M Tc-PYP imaging are depicted in Figures 1 and 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 The authors of the current study performed a retrospective analysis in 75 patients with suspected ATTR cardiac amyloidosis who underwent planar Tc99 m PYP cardiac imaging, 48 of whom were reported to have ATTR, 12 with endomyocardial biopsy-proven disease. Myocardial Tc99 m PYP uptake was evaluated on planar images using the established semiquantitative score 5 and the quantitative H/CL chest ratio, 6 although the authors used a semiquantitative score threshold of C1, not C2, for detecting ATTR, in part because they used a 3 hour, not 1 hour, imaging time (see below). They found that both the Tc99m PYP semiquantitative score and H/CL ratio were associated with mortality with HRs of 1.49 (95% CI 1.08-2.08, P = 0.016) and 5.19 (95% CI 1.46-18.4, P = 0.0111), respectively, and with death or heart failure hospitalization with HRs of 1.49 (95% CI 1.17-1.90) and 3.15 (95% CI 1.21-8.23), respectively.…”
mentioning
confidence: 99%